Analysis of organic farming practices in vegetable cultivation in Thiruvananthapuram district - Jaganathan D (Department of Agricultural Extension, College of Agriculture, 2004)
The study entitled “Analysis of organic farming practices in vegetable cultivation in Thiruvananthapuram district” was conducted with an objective of, to study the profile characteristics of the vegetable growers, to study the awareness, knowledge, attitude and adoption of organic farming practices, to find out the relationship between the profile characteristics and awareness, knowledge, attitude and adoption of organic farming practices and to identify the constraints in the adoption of organic farming practices and to suggest solutions to them. The study was conducted in Chenkal, Perumkadavila, Kalliyoor and Venganoor panchayats of Parassala, Aryancode, Pallichal and Neyyattinkara blocks respectively of Thiruvananthapuram district in Kerala. By using the proportionate random sampling technique 100 vegetable growers were selected. An explorative methodology was employed to identify the organic farming practices for the study. Twenty organic farming practices based on judges’ relevancy rating were finally selected. Fourteen independent variables were selected based on judges’ relevancy rating which included age, education, experience in vegetable cultivation, area under vegetable cultivation, livestock possession, mass media exposure, extension orientation, economic motivation, training attended, innovativeness, risk orientation, market perception, self confidence and environmental orientation. All these variables were quantified with the help of available measurement procedures. The dependent variables for the study were awareness, knowledge, attitude and adoption. These variables were quantified using measurement devices developed for the study. The relationship between the dependent variables and independent variables was studied using correlation analysis. Constraints in the adoption of organic farming practices were also recorded as perceived by the vegetable growers. The data were collected using a pre-tested structured interview schedule prepared for the study and non-participant observation technique by the researcher. The statistical tools like mean, percentage analysis, analysis of variance, correlation analysis and step wise regression analysis were used to analyse the data. The salient findings are presented below: Majority of the vegetable growers (48%) belonged to old age category. Most of the vegetable growers (52%) had secondary school education. Forty seven per cent of the respondents were having medium level of experience in vegetable cultivation. Most of the vegetable growers (64%) belonged to medium category with respect to area under vegetable cultivation. Nearly three fourth of the respondents had medium level of livestock possession. Sixty one per cent of the vegetable growers belonged to medium category with respect to mass media exposure. Most of the vegetable growers (70%) had medium level of extension orientation. A higher percentage of the respondents (71%) had medium level of economic motivation. Fifty seven per cent of the respondents had medium level of training followed by low level (33%). More than half of the respondents (55%) had medium level of innovativeness. Almost three fourth of the respondents (73%) had medium level of risk orientation. Fifty five percent of the respondents had medium level of market perception. Most of the vegetable growers (63%) belonged to medium category with respect to self confidence. Nearly three fourth of the respondents (72%) had high environmental orientation Majority of the respondents (73%) had medium level of awareness, seventy per cent of the respondents had medium level of knowledge, most of the respondents (64 %) had a favourable attitude and majority of the respondents (64 %) belonged to medium level of adoption of organic farming practices. Awareness about organic farming practices showed significant and positive relationship with education, mass media exposure, training attended, innovativeness, market perception, self-confidence and environmental orientation. Knowledge about organic farming practices was found to have significant and positive relationship with education, training attended, innovativeness, risk orientation, self confidence, environmental orientation and awareness. Seven variables, namely, mass media exposure, innovativeness, market perception, self confidence, environmental orientation, awareness and knowledge showed a significant and positive relationship with attitude towards organic farming practices. Nine variables namely, education, mass media exposure, training attended, innovativeness, self confidence, environmental orientation, awareness, knowledge and attitude showed a significant and positive relationship with adoption of organic farming practices. The step-wise regression analysis showed that extent of adoption of organic farming practices was greatly influenced by knowledge, environmental orientation and awareness of vegetable growers. Most important constraint perceived by the vegetable growers was the non-availability of inputs. The other important constraints were lack of information, lack of sufficient good quality seeds, high cost of inputs, extensive prevalence of pests and diseases and lack of credit facilities. Organic farming in vegetable cultivation is a viable alternative because it enlivens the soil, strengthens the natural resource base and sustains biological production. The efforts from research, extension, supply of inputs and development of market channels for production of organic vegetables are needed to facilitate the successful adoption of organic farming practices by the vegetable growers. Therefore, action plans for developing organic farming should be part of a larger plan for nature conservation and health of the community and the land. It is genuinely hoped that organic farming will emerge in adding life and greenery to the field of agriculture and brightness to the farmers’ faces.